Estimating Genetic Parameters to Enhance Brahman Cattle Performance in Indonesia - A. Anang; H. Indrijani; M. H. Zulkarnaen (Tropical Animal Science Journal, 2026)
Brahman cattle represent a critical resource for beef production in Indonesia, necessitating a comprehensive genetic improvement program to meet commercial demand and customer preferences. This study aimed to estimate genetic parameters and predict breeding values for body weight measured at different ages in the Indonesian Nucleus Breeding Centre located in Sembawa, Sumatra. The dataset comprised 1,082 records from 32 sires and 552 dams. Body weight measurements were obtained at birth, weaning, yearling, and 18 months of age. The fixed effects of sex and parity were analyzed by using a general linear model to determine levels of significance. Genetic parameters—including heritability and breeding values—were estimated using restricted maximum likelihood and best linear unbiased prediction. Two models were fitted: one incorporating only the additive genetic effect and another integrating both additive and maternal genetic effects. The results showed heritability estimates from the additive-only model ranged from 0.571 to 0.674, while estimates from the model that included additive and maternal genetic effects ranged between 0.426 and 0.501. There was substantial maternal influence on offspring performance across all ages, resulting in upwardly biased heritability estimates when only additive genetic effects were considered. For accurate genetic evaluation and reliable prediction of breeding values, the inclusion of maternal genetic effects in the analytical model is strongly recommended to optimize genetic gain in breeding programs.